Grace and agency in Paul and second temple judaism : interpreting the transformation of the heart - Wells, Kyle B. 1980- (Novum Testamentum, Supplements, 2015)
Following recent intertextual studies, Kyle B. Wells examines how descriptions of 'heart-transformation' in Deut 30, Jer 31-32 and Ezek 36 informed Paul and his contemporaries' articulations about grace and agency. Beyond advancing our understanding of how these restoration narratives were interpreted in the LXX, the Dead Sea Literature, Baruch, Jubilees, 2 Baruch, 4 Ezra, and Philo, Wells demonstrates that while most Jews in this period did not set divine and human agency in competition with one another, their constructions differed markedly and this would have contributed to vehement disagreements among them. While not sui generis in every respect, Paul's own convictions about grace and agency appear radical due to the way he reconfigures these concepts in relation to Christ.